Teaching Reading Using PQRST Method with Power Point Media - Feri Huda; M. Alimul Huda (Journal of Development Research, 2022)
The problem with student reading comprehension is that it is difficult to translate reading comprehension sentences, as English contains multiple tenses as well as vocabulary. Many students often find it difficult due to poor grammatical structure and vocabulary. Teaching methods are usually not very interesting for students. They say the instructor uses the traditional method (GTM). One alternative solution to this problem is PQRST with PowerPoint media. This method has been studied to see if it works effectively for learning to read. This study adopted a quasi-experimental procedure using a non-randomized pre-test and post-test design. As a result, it was found that the PQRST method using PowerPoint media is an effective method for reading comprehension instruction because it exhibits better reading comprehension than the conventional method.Keywords: teaching reading, PQRST, PowerPoint